The Development of Science Module Integrated with Ethnoscience of Singo Barong Mask to Improve Scientific Literacy and Cultural Preservation Attitudes - Jihan Jihannita; Wirawan Fadly; Rahmi Faradisya Ekapti; Dewi Luthfiana; Asri Widowati (Yayasan Keluarga Guru Mandiri, 2024)
The low achievement of scientific literacy and the attitude of cultural preservation requires innovation in implementing science education in schools. This research aims to develop integrated science modules on Singo Barong mask ethnoscience teaching materials to improve scientific literacy and cultural preservation attitudes. This study measures the feasibility of the module and its effectiveness in improving scientific literacy and cultural preservation attitudes. This research used Borgh and Gall’s (1960) model with six stages. The study was conducted in class VII using a non-equivalent one-group pretest-posttest trial design. The results of module effectiveness are obtained from the pretest-posttest analysis of students. The instruments given were in the form of scientific literacy questions and cultural preservation attitude questionnaires. Based on the analysis of scientific literacy and cultural preservation attitudes, students using the developed modules have increased, as indicated by the gain value obtained in the medium category. The results of module validation are carried out by four expert lecturers and one science teacher, and practicality assessment by students. The results of feasibility and practicality obtained excellent assessment. In conclusion, the integrated science module of Singo Barong mask ethnoscience is suitable for the science learning process to improve scientific literacy and cultural preservation attitudes.